Technology Usage and Academic Performance in the Pisa 2018 Report - Oscar Navarro-Martinez; Beatriz Peña-Acuña (Springer, 2022)
In the last two decades, the great technological advances sweeping society have made inroads into the educational sphere. The use of information and communication technology and social networks has opened up new possibilities for student learning, which require appropriate treatment by family and teachers. This quantitative study takes a new approach to investigating the relationship between Spanish teenage students' academic success and their use of technology and social networks. It analyses data published in the 2018 PISA report to assess whether the use of these resources is appropriate, and to determine their impact on students' learning and performance in reading, mathematics and science. The study takes a new approach in terms of the variables selected and the analysis of the data through two statistical measures. The results suggest that excessive use of technology and social networks, both during the week and at weekends, impairs performance. This finding is more acute in the case of male students, as the data indicates that they start at an earlier age and are more likely to use social media for the detrimental activity of online gaming.